Triceps surae muscle-tendon unit mechanical property changes during 10 minutes of streching. (July 2021) - Borges, Mariana; Cini, Anelize; Sonda, Francesca Chaida; Souza da Rocha, Emmanuel; Felappi, Cassiele Janina; Vaz, Marco Aurélio; Lima, Cláudia Silveira
Abstract: Objective: To verify the effect of 10-min static stretching on the triceps surae mechanical properties. Design : Quasi-experimental one-group pre test-post test study compared the time points of before, after, and minute by minute of one session of triceps surae passive static stretching. Methods: 15 participants performed a 10-min plantar flexor passive static stretching on the isokinetic dynamometer. We evaluated passive torque and myotendinous junction (MTJ) displacement before, minute by minute, and after the intervention. In contrast, we evaluated the range of motion (ROM), passive torque, MTJ displacement, and hysteresis before and after the intervention. Paired t -test compared pre and post-intervention time points. Passive torque and MTJ displacement in the minute-by-minute evaluations were compared by repeated measures one-way ANOVA with a Bonferroni post-hoc test. Results: ROM increased (effect size d  = 0.56) and passive torque and muscle-tendon unit stiffness decreased (effect size d  = 0.65 and d  = 0.73, respectively) post-stretching. There was a reduction only in passive torque in the minute-by-minute evaluation, mainly at minutes five and seven. Conclusions: passive torque decreased over a 10-min static stretching session of the ankle plantar flexors, followed by a ROM increase and muscle-tendon unit, a stiffness decrease.